THE EFFECT OF TACIT KNOWLEDGE SHARING ON INNOVATIVE WORK BEHAVIOR: BIG PERSONALITY, MOTIVATION, SELF-EFFICIENCY AND TRUST AS ANTACEDENTS (Study on the Academic Staff of the Surakarta Batik Islamic University) - Rosyida Nur Laili; Sinto Sunaryo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Work Behavior: Big Personality, Motivation, Self-Efficacy and Trust as Antecedents (Study on Academic Staff of the Islamic University of Batik Surakarta). This research method uses quantitative methods with a total population of UNIBA academic staff100 personnel. The sampling technique for this study used non-probability sampling by taking samples from all of the respondent's data. Data collection techniques using questionnaires that will be givenUNIBA academic staff. The data analysis tool uses the Smart-PLS application. The research results show thatextraversion variable has a positive effect on tacit knowledge sharing, conscientiousness variable has a positive effect on tacit knowledge sharing, agreeableness variable has a positive effect on tacit knowledge sharing, emotional stability variable has a positive effect on tacit knowledge sharing, openness variable has a positive effect on tacit knowledge sharing, motivation variable has a positive effect on tacit knowledge sharing, self-efficacy variable has a positive effect on tacit knowledge sharing, trust variable has a positive effect on tacit knowledge sharing, tacit knowledge sharing variable has a positive effect on innovative work behavior. Keywords: Tacit Knowledge Sharing, Extraversion, Conscientiousness, Agreeableness, Emotional Stability, Openness, Motivation, Self-Efficacy, Trust, Innovative Work Behavior